Battery storage for renewables : market status and technology outlook - Kempener, Ruud; Borden, Eric (International Renewable Energy Agency, 2015)
Energy storage capabilities are crucial for the integration of high levels variable renewable sources, such as solar and wind energy, onto the power grid. This report shows that battery storage technologies for renewable energy are already cost-competitive for island and rural applications. Furthermore, the market for battery storage systems coupled with rooftop solar panels has started growing rapidly. The report is accompanied by 12 case studies on battery storage systems around the world.